Bone-Peg Grafting for Osteochondritis Dissecans of the Humeral Capitellum. (April 2016) - Maruyama, Masahiro; Harada, Mikio; Satake, Hiroshi; Uno, Tomohiro; Takagi, Michiaki; Takahara, Masatoshi
Purpose: To review the outcome of bone-peg grafting for osteochondritis dissecans (OCD) grade II lesions of the humeral capitellum. Methods: Records of 10 male adolescent baseball players aged 10 to 15 (mean, 12.3) years who underwent bone-peg grafting for OCD grade II lesions of the humeral capitellum of the dominant arm were reviewed. The mean time from symptom onset to presentation was 11 (range, 1–36) months. The mean duration of conservative treatment was 5 (range, 1–25) months. The mean time from symptom onset to surgery was 17 (range, 3–39) months; it was >6 months in 6 patients. The mean size of the lesions was 13×14 mm. Patients were assessed for elbow pain, range of elbow and forearm motion, Timmerman-Andrews elbow score, return to sports activity level, and radiographic evidence of healing, osteoarthritic changes, and radial head hypertrophy. Results: The mean follow-up period was 25 (range, 10–52) months. Postoperatively, elbow pain was absent in 6, mild in 2, and moderate in 2 patients. The mean range of elbow motion changed from 136° to 139° (p=0.80). The mean Timmerman-Andrews elbow score improved from 163 to 189 (p=0.014); it was excellent in 7, good in 2, and fair in one patient. The mean extent of lesion healing was 71% (range, 33–100%). Five patients achieved complete healing after a mean of 5.2 (range, 5–6) months and returned to sports at a competitive level. The other 5 achieved partial healing of 33 to 56% (mean, 41%) that occurred laterally but not medially. Two of them returned to sports at a competitive level: one changed the throwing side and another had radial head hypertrophy. The remaining 3 underwent arthroscopic debridement of the unhealed lesion at 5, 10, and 15 months. One patient developed secondary osteoarthritis and further underwent costal osteochondral autografting 10 months later. None of the 5 patients with partial healing versus 4 of the 5 patients with complete healing underwent surgery within 6 months of symptom onset. All 3 patients with a dot at the interface versus 2 of the 6 patients with a line at the interface between the fragment and the lesion on MRI had complete healing. Conclusion: Bone-peg grafting is a viable option for OCD grade II lesions of the humeral capitellum when performed within 6 months of symptom onset and when the interface between the fragment and the lesion appears as a dot (rather than a line) on MRI.